Prognostic Significance of Visit-to-Visit Ultrafiltration Volume Variability in Hemodialysis Patients - Balázs Sági; Tibor Vas; Éva Fejes; Botond Csiky (Biomedicines)
Introduction: Patients on chronic hemodialysis (HD) have significantly higher mortality compared with the general population. Cardiovascular (CV) disease is the primary reason for death in these patients. Suboptimal extracellular fluid management increases the CV risk of HD patients. We aimed to study the effect of visit-to-visit ultrafiltration volume (UV) variability on CV events and mortality in chronic HD patients. Patients and Methods: In our study, 173 chronic HD patients were included (median age: 63 ± 13 years; 53% men). Ultrafiltration volume (UV) variability was analyzed retrospectively for 24 months. The standard deviation (SD) and coefficient of variation (CV) were calculated using the indices of UV variability. CV is the SD divided by the mean. The obtained parameters were SD and CV of the UV: UVSD and UVCV. UV data during the observation period were recorded and used to calculate UV variability. Routine transthoracal echocardiography was performed. Results: Patients were divided into groups based on the median of UVSD, low-UVSD (<568 mL) and high-UVSD (≥568 mL) group; and also based on the median of UVCV, low- (<0.29) and high-UVCV (≥0.29) group. All-cause mortality was significantly higher in the high compared to the low-UVSD (21/84 vs. 9/89; p < 0.001) group. Similarly, mortality was higher in the high-UVCV group compared to the low-UVCV group (18/78 vs. 12/95; p = 0.005) after 24 months. Major adverse CV event (MACE) rates were also significantly higher in the high- compared to the low-UVSD group (20/84 vs. 8/89; p < 0.001). Similarly, the MACE rate was significantly higher in the high-UVCV group compared to the low-UVCV group (15/78 vs. 13/95; p = 0.029) after 24 months. There was no significant difference between the groups in CV mortality. UVSD correlated with parathormone (PTH) level (r = 0.416; p = 0.015), and UVCV with total cholesterol (r = 0.419; p = 0.015). Left ventricular end-diastolic diameter (LVEDD) and end-systolic diameter (LVESD) were higher in the high-UVCV group compared to the low-UVCV group (49.95 vs. 52.08; p = 0.013 and 32.19 vs. 34.13; p = 0.034). Conclusions: According to our results, high UVSD and UVCD are associated with increased all-cause mortality and MACE rates but not CV mortality in chronic HD patients. Cardiovascular changes caused by increased UF volume variability during HD may contribute to higher CV morbidity and mortality in these patients.